Answer:
![(K.E_t)/(K.E_r) = 1](https://img.qammunity.org/2022/formulas/physics/college/o9ioo76ufjz6gmecqjp8van5b66s6ji12m.png)
Step-by-step explanation:
The translational kinetic energy of the hoop is given as:
---------------------- equation (1)
where,
= translational kinetic energy
m = mass of hoop
v = linear speed of hoop
The rotational kinetic energy of the hoop is given as:
![K.E_r = (1)/(2) I\omega^2](https://img.qammunity.org/2022/formulas/physics/college/kpkrf3337bhdvbz0i3iqzg1qqbu2soct8y.png)
where,
= rotational kinetic energy of the hoop
I = Moment of Inertia of the hoop = mr²
r = radius of the hoop
ω = angular speed of hoop =
![(v)/(r)](https://img.qammunity.org/2022/formulas/physics/college/77vg2fv4rjgjmkxv8fzbic8y8tiampvgpp.png)
Therefore,
------------------- equation (2)
dividing equation (1) and equation (2), we get:
![(K.E_t)/(K.E_r) = ((1)/(2)mv^2 )/((1)/(2)mv^2 )\\\\(K.E_t)/(K.E_r) = 1](https://img.qammunity.org/2022/formulas/physics/college/8t7783gycoiz7tdiyq7kv9pmxg5j2ce9uc.png)